Coexistence of accompanying autoimmune diseases in adolescents with autoimmune thyroiditis - V.I. Pankiv (Zdorovʹe Rebenka)
Background. Autoimmune thyroiditis (AIT) is the most common cause of goiter and acquired hypothyroidism in children and adolescents living in iodine-sufficient regions. Most studies, which investigated the coexistence of AIT and other autoimmune diseases, were conducted in the adult patient population, and examined the prevalence of AIT in nonthyroid autoimmune diseases. The purpose of the study was to investigate the coexistence of other accompanying autoimmune diseases in adolescents aged 14–18 years who were diagnosed and followed up at the Ukrainian Scientific and Practical Centre of Endocrine Surgery, Transplantation of Endocrine Organs and Tissues of the Ministry of Health of Ukraine. Materials and methods. A total of 110 patients aged 14–18 years diagnosed with AIT were examined. Their age at admission, sex, family history, complaints at admission, comorbidities, physical examination and laboratory findings, clinical follow-up information were retrospectively reviewed. Results. Of the 110 patients, 74.6 % were female and 25.4 % were male, with a mean age of 15.9 ± 2.1 years. A total of 9 (8.2 %) of the patients had overt hypothyroidism, 29 (26.4 %) had subclinical hypothyroidism, and 72 (65.4 %) had euthyroidism. High level of thyroid peroxidase antibodies was detected in 108 (98.2 %) patients, and 81 (73.6 %) had high thyroglobulin antibody levels (Tg-Ab). There was a family history of autoimmune disease in 43.6 % of cases. Autoimmune diseases accompanying AIT were present in 29 (26.4 %) of patients. The most common of them were type 1 diabetes (17.3 %), celiac disease (2.7 %), skin diseases (8.2 %), and rheumatologic diseases (2.7 %). The mean age of AIT patients with and without concomitant autoimmune disease was similar. In both groups, female sex was dominant. The rate of subclinical hypothyroidism was statistically significantly elevated in the group without accompanying autoimmune disease (p < 0.001). A statistically significant relationship was found between elevated Tg-Ab and concomitant autoimmune disease. The prevalence of accompanying autoimmune disease was increased 2.34 times in patients with elevated Tg-Ab levels. Conclusions. Autoimmune diseases, especially T1DM and skin diseases, are associated with AIT. There is an increased risk of autoimmune disease in AIT that affects both sexes. Regular follow-up of AIT patients with elevated Tg-Ab levels for autoimmune disease development is important in terms of earlier diagnosis of diseases.